Mindfulness Exercise as a Strategy to Improve Learning Concentration in Physical Education for Elementary School Students - Karisdha Pradityana (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to examine the effectiveness of applying Mindfulness Exercise in enhancing students’ concentration. The significance of this research lies in its contribution to broadening insights into strategies for improving concentration through mindfulness-based practices. The research employed an experimental approach with a pre-experimental research design. The instrument used was a speed anticipation test, and data were analyzed quantitatively using normality testing (Shapiro–Wilk) and paired t-test. The findings revealed that prior to the intervention, the students’ concentration level was categorized as good in 0.00% of participants, whereas after the intervention, 90.00% of students achieved a good category, indicating an increase of 85.00%. Furthermore, the paired sample t-test yielded a significance value of 0.000 (p < 0.05), confirming a statistically significant improvement in student concentration following the application of Mindfulness Exercise. In conclusion, the application of Mindfulness Exercise has a positive and significant effect on improving student concentration. It is recommended that school principals consider these findings as a reference in decision-making related to teaching and learning strategies. Additionally, teachers are encouraged to implement Mindfulness Exercise as a preparatory activity prior to classroom learning to optimize students’ readiness and focus.